Patterns of Phytoindication Pollution of the Urban Environment the Maximum Width of the Leaves of the Silver Birch - Matveevich Mazurkin, Peter; A.I, Kudryashova (European Journal of Applied Sciences, 2019)
We offer indicators in the form of groups of at least 10 accounting leaves growing during the growing season, selected and marked with a white thread of birch hanging from the prevailing winds. Was previously obtained regularities in the behavior of leaves in the vegetation period from the date of Bud wood to the subsidence of each account sheet. The method of measuring the width of birch leaves in the growing season is proposed. It was found that before reaching the maximum length, width, perimeter and area of leaves with at least 10 measurements per season, the patterns vary along the growing branch of the biotechnical law. Therefore, in the summer of 2018, measurements were carried out in the city of Yoshkar-Ola, starting from July 15 to the maximum width of the sheet, as the most convenient for measuring the parameter of the accounting sheet. It turned out that the maximum width of the sheet depends on the growing conditions of the tree. The aim is to identify the patterns of phytoindication by measuring the width of birch leaves hanging during the growing season near the maximum concentration of sulfur dioxide and carbon, the level of radioactive background at various points near the roads with the greatest pollution. The regularities of the influence of these types of pollution on the average maximum width and vegetation time from may 1, 2018 to the maximum width of the registration sheet are obtained. It turned out that even in an ecologically clean city (10th place in Russia), low concentrations are about 25 times less than MPC, have a strong influence on the growth and development of birch leaves. Initially, with an increase in the concentration of three chemicals at eight points of the urban environment have a beneficial effect on the vegetation of leaves. With further increase in concentration there is a strong inhibition of growth and development of leaves. The proposed method is recommended for school environmental groups.